Baitouweng decoction alleviates ulcerative colitis by regulating tryptophan metabolism through DOPA decarboxylase promotion - Zhang, Junzhi; Lin, Binyan; Zhang, Ying; Hu, Xiaochao; Liu, Tongtong; Liu, E-Hu; Liu, Shijia (Frontiers in Pharmacology, 2024)
Background: Baitouweng decoction (BTW) is a classic botanical drugs formula that has been widely used clinically for the treatment of gut-related disorders in China.However, its role in ameliorating ulcerative colitis (UC) remains to be explored.The study aimed to determine the therapeutic efficacy and potential mechanism of action of BTW on dextran sodium sulfate (DSS)-induced colitis mice. Methods: In vivo: 3.5% DSS-induced experimental colitis mice were treated with BTW (Pulsatilla chinensis (Bunge) Regel, Phellodendron chinense C. K. Schneid, Coptis chinensis Franch and Fraxinus chinensis Roxb), kynurenine or DOPA decarboxylase (DDC) inhibitor (carbidopa). In vitro: Caco-2 cells were stimulated with TNF-α to activate inflammation and later treated with various concentrations of BTW and carbidopa. Model evaluation included body weight, disease activity index (DAI) score, colon length and histopathology. Cytokine levels were measured by flow cytometry. Protein levels were analyzed by proteomics and functionally annotated. The levels of tryptophan metabolites in mouse serum and colon were detected by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Alcian Blue/Phosphate Acid Schiff (AB/PAS) staining, immunohistochemistry and western blot were used to assess the intestinal barrier function and detect the protein expression levels. Results: BTW significantly reduced the DAI, ameliorated colonic injury and regulated inflammatory cytokines in DSS-induced colitis mice. The botanical drugs formula also promoted intestinal epithelial barrier repair by enhancing the expression of the tight junction (TJ) proteins. Tryptophan metabolic signaling pathway was significantly enriched in DSS-induced UC mice, and BTW decreased the level of kynurenine, increased indole metabolites. The therapeutic effect of BTW was evidently reduced when kynurenine was given to mice. Also, BTW promoted DDC protein expression and activated the aryl hydrocarbon receptor (AHR)/IL-22 signaling pathway. Conclusion: BTW improves ulcerative colitis by promoting DDC expression, regulating the conversion of tryptophan metabolism from the kynurenine pathway to the indole metabolism pathway, thereby modulating tryptophan metabolism to increase indole metabolites, and activating AHR receptors to restore intestinal barrier function.